2000
DOI: 10.1007/s150100070019
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ciprofloxacin-Resistant Escherichia coli in Hematologic-Oncologic Patients

Abstract: We propose that selective gut decontamination with ciprofloxacin should be discontinued as a routine measure for all neutropenic patients in the department under investigation. We propose waiving oral decontamination in low-risk patients with neutropenia of only a few days duration. For all other patients, a regimen with alternating prophylactic treatments of cotrimoxazol and a fluoroquinolone should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Many reports have documented the emergence of bacteria resistant to fluoroquinolones in units in which prophylaxis is practiced (e.g., see Cometta et al, Kern et al, Baum et al, and Razonable et al [24][25][26][27] ). There are no quantitative data indicating the extent to which patients came to harm as a result.…”
Section: Which Patients Should Be Offered Antibiotic Prophylaxis?mentioning
confidence: 99%
“…Many reports have documented the emergence of bacteria resistant to fluoroquinolones in units in which prophylaxis is practiced (e.g., see Cometta et al, Kern et al, Baum et al, and Razonable et al [24][25][26][27] ). There are no quantitative data indicating the extent to which patients came to harm as a result.…”
Section: Which Patients Should Be Offered Antibiotic Prophylaxis?mentioning
confidence: 99%
“…[2][3][4] Despite the logic of reducing bowel and mouth flora with antibiotics, thereby reducing the risk of subsequent bacteremia, there is no consensus that this is the right thing to do. [5][6][7][8] Preliminary work has even suggested that ciprofloxacin without metronidazole given as prophylaxis might promote development of graft-versus-host disease 9 and that ciprofloxacin alone may be associated with an increased risk of leukemia relapse among HSCT recipients. 10 In general, the infectious disease community, citing the concern of promoting drug resistance, has been hesitant about making this a routine approach, while the oncology community, with a specific patient in front of them whom they are trying to keep out of the hospital, has been more enthusiastic.…”
Section: Oral Prophylaxis: Background and Rationalementioning
confidence: 99%
“…However, for both infection control programs and research studies, this approach is often infeasible or impractical. Thus, hospital epidemiologists and researchers often rely on perirectal or rectal swabs to identify patients colonized with resistant organisms (1,2,8). Despite the widespread use of these approaches, no data exist describing their sensitivity and specificity for detection of resistant GNB compared to the gold standard of stool sample.…”
mentioning
confidence: 99%